Direction for Strengthening MSMEs in The IKN Support Area: Study of Issues and Expectations of Business Actors in Samboja and West Samboja, Kutai Kartanegara Regency - Indrayani, Indrayani; Hardaningrum, Tri Wahyu (Journal of Applied Business, Taxation and Economics Research, 2026)
The development of the new capital city, IKN Nusantara, has a significant impact on surrounding buffer areas, including Samboja and Samboja Barat, which are projected to become gateways for economic mobility, labor supply, and strategic supply chains that support the capital city. This study aims to explore and understand the dynamics, challenges, potentials, and capacity-building needs of MSMEs in responding to emerging economic opportunities generated by IKN development. This research applies a qualitative exploratory approach through written responses, Focus Group Discussion (FGD), observation, and documentation. The findings reveal that MSMEs possess substantial local potential, such as raw material availability, unique products, and expanding market prospects, yet continue to face limitations in access to capital, digital literacy, managerial skills, business legalization, and market competition. The study concludes that MSMEs require a comprehensive support ecosystem through capacity strengthening, strategic partnerships, and responsive policies to enable their role as economic pillars in the buffer areas of IKN. Recommendations include continuous mentoring, business digitalization, and the establishment of collaborative MSME networks across Samboja and Samboja Barat.